PERLINDUNGAN PEMBELI SATUAN RUMAH SUSUN ATAS PERJANJIAN PENGIKATAN JUAL BELI PRE PROJECT SELLING - Nadia, Prisya (Ensiklopedia Education Review, 2025)
Abstract: This study discusses the legal responsibility of housing developers for the Binding Sale and Purchase Agreement that has been made by housing developers and buyers with the pre-project selling method whose object has not been built or is still in the form of a site plan, as well as legal protection for buyers. The research was conducted using normative research methods and using case, legislative and conceptual approaches. The results of the study show that the responsibility of housing developers who do not carry out the content of the agreed agreement can be subject to criminal sanctions of imprisonment or fines for housing developers who do not follow according to the SOP (Standard Operating Procedure) and can be subject to administrative sanctions in the form of revocation of business licenses, consumers because they are not found out and it is the duty of housing developers to provide true information to consumers. Aggrieved buyers can sue the housing developer to the civil court to get legal protection.Keywords: Legal Responsibility, Pre-Project Selling, Legal Protection